Metastases to the Thyroid Presenting as a Metabolically Inactive Incidental Thyroid Nodule with Stable Size in 15 Months - Subhashini Yaturu; Raina A. Patel (Case Reports in Endocrinology)
Though the thyroid gland has a rich vascular supply, incidence of metastatic disease from distant organs is rare. Here we present an unusual case of metastases to the thyroid with several interesting features. A 63-year-old male with history of adenocarcinoma of the right lobe lung (5 years prior to presentation), treated with surgery and chemotherapy, followed by new adenosquamous lung cancer in the left lobe of the lung (one year prior to presentation), treated surgically followed by adjuvant chemotherapy, was referred to Endocrinology section for evaluation of an incidental thyroid nodule on CT chest. Ultrasound (US) of the thyroid revealed a complex, predominantly hypoechoic lesion measuring 1.8 cm within the lower pole of the right thyroid lobe and a subcentimeter lesion in the left lobe of the thyroid. Review of prior CT chests showed that the lesion in the right lobe was stable for 15 months, with no evidence of a hypermetabolic lesion on PET scan. The subcentimeter lesion was not seen on prior CT scans. US guided fine needle aspiration (FNA) and pathology of the lobectomy of the thyroid confirmed adenosquamous carcinoma. Interesting features in this case are that the thyroid metastases occurred without any evidence of synchronous lesions elsewhere, the size was stable over 15 months, and the lesions were metabolically inactive.